Evaluation and Calibration of CBCT Reconstruction Models - Gao, Tao; Sun, Yuchun; Yuan, Fusong; Liang, Shanshan (Current Medical Imaging, 2023)
Purpose: This study proposes a method for improving the accuracy of three-dimensional (3D) models generated through cone-beam computed tomography (CBCT). Methods: A 3D cuboid model fitted with a ¼-scale dentition on its top surface was constructed to simulate an alveolar bone with teeth. A physical specimen of the model was printed and the distance between its opposite sides was measured using a vernier caliper. The physical model was light-scanned, and the surface data of the generated 3D model were corrected by calibrating the distance between opposite sides against the vernier caliper measurements. The physical model was also scanned using CBCT to reconstruct a second 3D model. The overall deviation between the two models and the distance deviation in each direction of the cuboid and dentition were quantified and statistically analyzed. Results: The overall deviation between the reconstructed CBCT model and the calibrated structured light-scanned model was 0.098 ± 0.001 mm. Following calibration, the overall deviation was 0.010 ± 0.006 mm. A one-way variance analysis suggested that the overall deviations' differences were not statistically significant (P < 0.05). Conclusion: This study lays a solid foundation for accurate dental implantation.
Keywords: implantation